Plastic waste management: Need for a paradigm shift in Malaysia - P, Agamuthu. (Malaysian Journal of Science, 2004)
Over the last century, plastics have become a major new material used widely for a variety of products world wide, including replacements for human body parts, to the construction of supersonic aircraft and spacecraft. The growth of plastic production has taken place at the expense of more traditional materials, such as steel, aluminium, paper and glass. It is estimated that 30% of used plastics are eventually discarded into the environment, and since conventional plastics are produced from petrochemical compounds and are non-biodegradable it becomes an environmental hazard when land- filled. Plastic waste generated and quantity generated is a growing concern in many developing countries, including Malaysia. Plastic industry in Malaysia, which began in 1950, registered a 15% growth per— annum. The plastics produced are mainly used by the packaging industry (35%), while electrical and electronic industn used 30%. Other users are households (12%), automotive industry (8%) and construction (7%). Concurrently, the total resin consumption has reached 1.20 million metric tons in 2000. while the per capita consumption increased from 20kg in 1989 to 55 kg in 1997. It is estimated to reach 60kg in 2003. The growth is expected to continue and the plastic industry is projected to achieve double-digit growth for the fourth consecutive year in 2002. In the year 2000, Malaysians used about 600.000 tonnes of plastics, while recycling was extremely low. Hence, 99.99% of the household plastics end-up in the 144 landfills. Plastic components in the Municipal Solid Waste (MSW) from urban areas average 18%. but in some areas (Labuan) it can go as high as 48%. Research in plastics is concentrated in the development of bioplastics using renewable resources and organic waste. Since the costs of bioplastics are currently much higher than conventional plastics due to raw materials costs and production expenses, hence the need to use materials that are available at low cost, such as palm oil mill effluent and kitchen waste. Biodegradability of degradable plastics (Environmentally Degradable plastic, EDP) is another area of scientific investigations. Results obtained from oxidative exposure, composting trials and microbial anahsis showed positively EDP is biodegradable. Physical and chemical analysis, including Fourier Transform Infra Red (FTIR) spectrum confirmed the biodegradability